Designing a BDI agent reactant model of behavioural change intervention - Adegoke, Ojeniyi; Ab. Aziz, Azizi; Yusof, Yuhanis (Penerbit UTM Press, 2015)
Belief-Desire-Intention (BDI) model is well suited for describing agent’s mental state. The BDI of an agent represents its motivational stance and are the main determinant of agent’s actions.Therefore, explicit understanding of the representation and modelling of such motivational stance plays a central role in designing BDI agent with successful behavioral change interventions. Nevertheless, existing BDI agent models do not represent agent’s behavioral factors explicitly. This leads to a gap between design and implementation where psychological reactance has being identified as the cause of BDI agent behavioral change interventions failure. Hence, this paper presents a generic representation of BDI agent model based on behavioral change and psychological theories.Also, using mathematical analysis the model was evaluated. The objective of the proposed BDI agent model is to bridge the gap between agent design and implementation for successful agent-based interventions.The model will be realized in an agent based application that motivates children towards oral hygiene. The study explicitly depicts how agent’s behavioral factors interact to enhance behavior change which will assist agent-based intervention designers to be able to design intervention that will be void of reactance.